A comparison of adding liraglutide versus a single daily dose of insulin aspart to insulin degludec in subjects with type 2 diabetes (BEGIN: VICTOZA ADD‐ON). Issue 7 (11th February 2014) - Mathieu, C.; Rodbard, H. W.; Cariou, B.; Handelsman, Y.; Philis‐Tsimikas, A.; Ocampo Francisco, A. M.; Rana, A.; Zinman, B.; on behalf of the BEGIN: VICTOZA ADD‐ON (NN1250‐3948) study group
<x xml:space="preserve">Abstract</x> Aim Two treatment strategies were compared in patients with type 2 diabetes (T2DM) on basal insulin requiring intensification: addition of once‐daily (OD) liraglutide (Lira) or OD insulin aspart (IAsp) with largest meal. Methods Subjects completing 104 weeks (52‐week main trial BEGIN ONCE‐LONG + 52‐week extension) on insulin degludec (IDeg) OD + metformin with HbA1c ≥ 7.0% (≥53 mmol/mol) were randomized to IDeg+Lira [n = 88, mean HbA1c: 7.7% (61 mmol/mol)] or IDeg+IAsp (n = 89, mean HbA1c: 7.7%) for 26 weeks, continuing metformin. Subjects completing 104 weeks with HbA1c <7.0% continued IDeg + metformin in a third, non‐randomized arm (n = 236). Results IDeg+Lira reduced HbA1c (−0.74%‐points) significantly more than IDeg+IAsp (−0.39%‐points); estimated treatment difference (ETD) (IDeg+Lira−IDeg+IAsp) −0.32%‐points (95% CI −0.53; −0.12); p = 0.0024. More IDeg+Lira (49.4%) than IDeg+IAsp (7.2%) subjects achieved HbA1c <7.0% without confirmed hypoglycaemia [plasma glucose <3.1 mmol/l (<56 mg/dl) or severe hypoglycaemia) and without weight gain; estimated odds ratio (IDeg+Lira/IDeg+IAsp) 13.79 (95% CI 5.24; 36.28); p < 0.0001. IDeg+Lira subjects had significantly less confirmed and nocturnal confirmed hypoglycaemia, and significantly greater weight loss (−2.8 kg) versus IDeg+IAsp (+0.9 kg); ETD (IDeg+Lira−IDeg+IAsp) −3.75 kg (95% CI −4.70; −2.79); p < 0.0001. Other than more gastrointestinal side effects with IDeg+Lira, no safety differences occurred. Durability of IDeg was established in the non‐randomized arm, as mean HbA1c remained <7.0% [mean 6.5% (48 mmol/mol) at end‐of‐trial]. Conclusions IDeg+Lira improved long‐term glycaemic control, with weight loss and less hypoglycaemia versus adding a single daily dose of IAsp in patients with T2DM inadequately controlled with IDeg + metformin.